„THE KNOTTED CORD” JERZEGO PIETRKIEWICZA NA TLE BRYTYJSKIEJ POWIEŚCI KATOLICKIEJ - Cieplińska, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Knotted Cord, published in 1953 both in London and New York, was the first novel written in English by a Pole, Jerzy Pietrkiewicz. The author related to the conventions of contemporary British novel, which made the book a success. The Catholic outlook – full of axiological dualism – was one of the elements, which made the book closer to the sensibility of a reader brought up within the Anglosaxon culture. Strongly emphasised religious plot in the Knotted cord only confirms the thesis that Pietrkiewicz made an attempt to enter British literature as a Catholic writer, as Catholic novel was one of the characteristic trends of literature in the 50. of the XX century in the United Kingdom.